Competition Limit at the Level of Public Markets - Khadri, Hamza; Diaf, Yassamina (Journal of Legal Studies and Researches, 2020)
This study sheds the light on researching the degree on which the principle of competition is applied in dealing with public deals in the light of Presidential Decree No. 15/247 of September 16th , 2015,which includes the organization of public deals and public utilities delegations. Laws related to public deals are discussed regarding its two parts. relying on advertising to determine the existence or absence of competition.